Spin-reorientation phase transition in ferrite-garnet films of different axial anisotropy - Mamalui, Ju.A.; Siryuk, Ju.A.; Bezus, A.V. (Functional Materials, 2012)
The mechanism of spin-reorientation phase transition (SRPT) in ferrite-garnet films has been studied. Changes in structure of domain boundaries during phase transition have been investigated. Domain structure models appropriate for the experiment have been proposed. It has been shown that the phase transition through nucleation in the domain boundary induced the first-order phase transition from axial to angular phase. The SRPT mechanism does not depend on the value of ratio between anisotropy constants.